Reliabilitas Tes Buatan Guru Mata Pelajaran Matematika Menurut Teori Tes Klasik Tingkat SMP Di Kota Baubau - Rasmuin Rasmuin; Ernawati Jais; Anak Agung Sri Mega Wahyuni (Jurnal Akademik Pendidikan Matematika, 2021)
Problem statement of this research was how cordthe level of reliability of the test mede by Mathematics teacher at the Junior High School Level in Baubau City according to the Classical Test Theory. Objective of this research was to analysis and to describe the level of reliability of the test made by Mathematics teacher at the Junior High School Level in Baubau City according to the Classical Test Theory. This research used quantitative research according to the Classical Test Theory. Data collection technique in this research used research instrument of multiple choice answer sheet at Junior High School student in VIII grade who took the end of the even semester test for Mathematics for the 2020/2021 academic year along with the answer key using ITEMAN application. Based on the research outcome, it was concluded that the level of reliability of the test made by Mathematics teacher according to the Classical Test Theory at the Junior High Schoool Level in Baubau City which was analyzed by the ITEMAN program had a reliability level based on the criteria category consisting of 7 school namely SMP Negeri 4 Baubau was 0.844 > 0.600 very high category, SMP Negeri 2 Baubau was 0.719 > 0.600 and SMP Negeri 18 Baubau was 0.778 > 0.600 high category, SMP Negeri 8 Baubau was 0.410 > 0.600 enough category, SMP Negeri 10 Baubau was 0.337 < 0.600 low category, SMP Negeri 6 Baubau was -0.173 and SMP Negeri 16 Baubau was -0.448 < 0 unreliable category.